Strengthening Service Leadership, Organizational Culture, Interpersonal Communication And Perceived Organizational Support (POS) In An Effort To Improve Organizational Citizenship Behavior (OCB) - Renata, Dian; Setyaningsih, Sri; Wulandari, Dian (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
This research examines strategies for improving Organizational Citizenship Behavior (OCB) among teachers by strengthening Servant Leadership, Organizational Culture, Interpersonal Communication, and Perceived Organizational Support (POS). The study, conducted in a private high school in Depok, Indonesia, utilizes a quantitative approach and path analysis to evaluate the direct and indirect effects of these variables on OCB. The results show that Servant Leadership, Organizational Culture, Interpersonal Communication, and POS all have direct positive and significant effects on OCB. Additionally, POS acts as an effective intervening variable, enhancing the impact of Servant Leadership, Organizational Culture, and Interpersonal Communication on OCB. The research findings suggest that fostering these factors can significantly improve OCB, which in turn enhances organizational effectiveness and the overall educational environment. The SITOREM analysis further identifies key indicators that need strengthening to optimize the strategies for increasing OCB in educational settings.